(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to evaluate the anthropometric profile of 36 athletes participating in the sport of soccer a college sport, aged between 15 and 19 years. The analyzed parameters were Body Mass Index (BMI), height, weight and axial medium, triciptal and subescapular skinfold thickness. The results, presented as the mean + standard deviation, were respectively 22.7 + 1.8 kg/m²; 177.2 + 6.9 cm; 71.3 + 8.7 kg; 13.9 + 3.3 mm²; 7.4 + 2.04 mm²; 7.9 + 2.2mm². According to the values we consider the group to be within the normality range for the various parameters. Nevertheless, for the BMI classification, it was observed that 6 athletes (16.7%) were classified as overweight. This parameter is not suitable for athlete classification since physical activity practice increases the lean body mass and, consequently, the body weight. The high energy demands of training or competition and the studied age groups, as some athletes have not gone through puberty, require players to consume a balanced diet. It is necessary to investigate the dietary intake of these athletes with further individualized nutrition guidance to correct possible dietary inadequacies with the goal of improving physical performance and quality of life.